2020
DOI: 10.1111/os.12803
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Model of Bone Angiosarcoma Patients: A Population‐based Analysis of Epidemiology, Prognosis, and Treatment

Abstract: Objective: To investigate the epidemiological data, prognostic factors, and treatment outcomes of bone angiosarcoma (BA). Methods: This retrospective study was based on the Surveillance, Epidemiology, and End Results (SEER) database. The medical records of BA patients were selected from the SEER database from 1975 to 2016. Variables including patients' baseline demographics (age, sex, marital status, and year of diagnosis), tumor characteristics (tumor size, grade, and SEER Historic Stage A), and treatment (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…As for the histologic grade, a recent study concluded AS with grade III histology tended to experience a shorter survival which was consistent with our result 15 . The median survival time of AS was various in different primary sites 16 18 , but which site with the highest mortality has not been well documented. Our study elaborated AS from heart mediastinum harbored the highest risk compared with soft tissue, bone and peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…As for the histologic grade, a recent study concluded AS with grade III histology tended to experience a shorter survival which was consistent with our result 15 . The median survival time of AS was various in different primary sites 16 18 , but which site with the highest mortality has not been well documented. Our study elaborated AS from heart mediastinum harbored the highest risk compared with soft tissue, bone and peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…It also indirectly led to a poor prognosis for the elderly patients. In fact, morbidity and mortality increase with age in many solid tumors 33,34 . The clinical factors used in the nomogram to predict OS in patients with AS included age.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, morbidity and mortality increase with age in many solid tumors. 33 , 34 The clinical factors used in the nomogram to predict OS in patients with AS included age. In our study, stage was also identified as an important prognostic factor and it was used for the calculation of nomograms for OS and CSS.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue sarcomas (STSs) account for approximately 1% of all malignancies in adults and have more than a hundred subtypes 1–4 . An estimated 13,460 new STS diagnoses were made in the U.S. in 2021, along with 5350 related deaths 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Soft tissue sarcomas (STSs) account for approximately 1% of all malignancies in adults and have more than a hundred subtypes. 1 , 2 , 3 , 4 An estimated 13,460 new STS diagnoses were made in the U.S. in 2021, along with 5350 related deaths. 5 The common histotypes include liposarcoma, leiomyosarcoma, and undifferentiated pleomorphic sarcoma, with the most typical primary sites being the extremities (40%–50%), trunk (13%), and retroperitoneal space (7%).…”
Section: Introductionmentioning
confidence: 99%